Reviewer acknowledgements for Journal of Bahasa & Sastra, Vol.15, No.1, April 2015 - Sukyadi, Didi (Jurnal Pendidikan Bahasa dan Sastra, 2015)
Â Reviewer AcknowledgementsJournal of Â bahasa sastra wishes to acknowledge the following individuals for their assistance with peer review of manuscripts for this issue. Their help and contributions in maintaining the quality of the journal are greatly appreciated.